2011
DOI: 10.1111/j.1750-3841.2011.02440.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Chilling Methods on Meat Quality and Calpain Activity of Pork Muscle Longissimus Dorsi

Abstract: Conventional and RC methods are commonly used for pork in commercial practice nowadays. Compared with conventional chilling, the effect of RC on quality parameters of pork varies. In recent years, short-duration chilling (SC) is widely used in many Chinese pig slaughtering facilities. However, few researchers have studied the effect of SD on pork quality. Therefore, the present study investigated the effect of different chilling methods on functionalities or quality of chilled pork meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The instrumental color characteristics ( L *, a * and b * values) are highly correlated with the visual redness of fresh meat. Therefore, it is an important factor in predicting consumer self‐reported purchase intent of chilled fresh pork . The effects of the ZnO nanoparticle‐coated film on cold meat color are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrumental color characteristics ( L *, a * and b * values) are highly correlated with the visual redness of fresh meat. Therefore, it is an important factor in predicting consumer self‐reported purchase intent of chilled fresh pork . The effects of the ZnO nanoparticle‐coated film on cold meat color are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The WHC of each pork sample was determined using cooking loss and pressing loss methods. 18 Each meat sample was weighed (W 1 ) and individually placed inside a polyethylene bag, followed by cooking in a water bath at 80 ∘ C for 30 min. The cooked samples were then cooled at 4 ∘ C for 16 h in a refrigerator.…”
Section: Determination Of Whcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, a lot of research has been performed to understand the effects of accelerated air chilling on pork quality. Several studies have demonstrated that application of accelerated chilling has an impact on pork quality with beneficial effects on the rate of pH decline, color, and drip loss (Rybarczyk, Karamucki, Pietruszka, Rybak, & Matysiak, ; Springer, Carr, Ramsey, & Miller, ; Xu, Huang, Huang, Xu, & Zhou, ; Zhang, Peng, Zhou, Xu, & Wu, ) but not all effects were fully consistent across the studies. The impact of chilling on meat quality has been comprehensively reviewed by Savell et al (), James and James () and Przybylski, Regenstein, and Zybert ().…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to predict pork quality due to many of factors to affect the quality. Fresh meat quality is the result of postmortem muscle metabolism, which is influenced by various management conditions such as transport, pre-slaughter handling, stunning, and processing and cooling conditions for carcasses (Rosenvold and Anderson, 2003;Pearce et al, 2011;Xu et al, 2012;Marija et al, 2014). Thus there is no single definition for high quality meat applied in the pork industry to date.…”
Section: Introductionmentioning
confidence: 99%